ECONOMIC LOSSES DUE TO HELMINTH PARASITES IN SHEEP - P. Yavari; K.Mohammad; A. Eslami (Tehran University of Medical Sciences, 1986)
Investigation was carried out in order to determine the economic benefits from therapy of gastrointestinal helminthosis and fasciolosis in almbs of Mazandaran Province of Iran. The study included 72 Lambs and the economic benefits were measured in the basis of weight gain. The lambs were divided into a control and therapy groups. The therapy groups received antihelminthics and our lambs were evaluated over a 9 months period at 3 intervals. The results clearly showed a high rate of infestation and that effective therapy with tetramizole for gastroin intestinal helminthoses led to an average weight gain of 1.23 kg over 9 months as compared to controls. This was statistically significant at P